2015
DOI: 10.1007/s11692-015-9329-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and Age is Positively Related to Brain Size in Andrew’s Toad (Bufo andrewsi)

Abstract: The Expensive Brain Framework (EBF) and the Cognitive Buffer Hypothesis are commonly used to explain inter-and intraspecific variation in brain size and brain architecture. Using Andrew's toad (Bufo andrewsi) as a model species, we investigated whether brain attributes in amphibians are shaped by the interplay between age and the length of the activity season as determined by altitude and latitude. We found significant differences in absolute and relative brain volume across 12 populations. Supporting the EBF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…The majority of hibernating species, however, spends at least one‐third to one‐half of their total lifetime in hibernation and is therefore expected to exhibit relatively small brains. Support for this hypothesis derives not only from the present study but also from an intraspecific study in Andrew's toads ( Bufo andrewsi ), which found that populations with longer periods of hibernation had smaller brains (Jiang et al ., ). Furthermore, a study in extant and extinct bear species reveals that brain size is smaller in species that exhibit dormancy and have a low calorie diet (Veitschegger, ).…”
Section: Discussionmentioning
confidence: 97%
“…The majority of hibernating species, however, spends at least one‐third to one‐half of their total lifetime in hibernation and is therefore expected to exhibit relatively small brains. Support for this hypothesis derives not only from the present study but also from an intraspecific study in Andrew's toads ( Bufo andrewsi ), which found that populations with longer periods of hibernation had smaller brains (Jiang et al ., ). Furthermore, a study in extant and extinct bear species reveals that brain size is smaller in species that exhibit dormancy and have a low calorie diet (Veitschegger, ).…”
Section: Discussionmentioning
confidence: 97%
“…Mosaic‐like brain evolution has been documented in sensory areas across a wide variety of taxa (Baron et al ., ; Ranade et al ., ), and also at intraspecific level among populations inhabiting different environments (e.g. Gonda et al ., ; Jiang et al ., ). Hence, further analysis of the anuran brain architecture extending to species occurring in contrasting habitats is likely to uncover further evidence supporting mosaic evolution hypothesis of brain evolution.…”
Section: Discussionmentioning
confidence: 97%
“…Here we aimed to verify the predictions of the CBH and the EBH by investigating patterns of variation in brain size and brain structures such as comparative volume of olfactory nerves, olfactory bulbs, telencephalon, optic tectum and cerebellum across six F. limnocharis populations from different altitudes and latitudes along a latitudinal and altitudinal transect in China. Consistent with the EBH, B. andrewsi living at lower latitudes and/or altitudes have larger absolute and relative brain volume (Jiang et al ., ). We hypothesized that the Asian grass frogs would develop larger brains in lower latitudes and/or altitudes.…”
Section: Introductionmentioning
confidence: 97%
“…Many physiological and behavioral adaptations of animals reflect environmental conditions. Indeed, it is known that the variability in environmental conditions over time is important for brain size evolution (Sol, Lefebvre & Rodriguez‐Teijeiro, ; Schuck‐Paim, Alonso & Ottoni, ; Roth et al ., ; van Woerden, van Schaik & Isler, ; van Woerden et al ., ; Jiang et al ., ). Two hypotheses – the cognitive buffer hypothesis (CBH) and the expensive brain hypothesis (EBH) – have focused on explaining the relationships between the evolution of brain size and seasonality of habitats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation